Impact of Paradoxical Leadership on Employee Creativity: Moderating Role of Employee Mindfulness and Mediating role of Absorptive Capacity - Idrees, Saba; Bhatti, Asim; Ali, Madiha (Dialogue Social Science Review (DSSR), 2025)
Paradoxical Leadership Behavior (PLB) provides a promising venue to face the organizational challenges as the traditional styles of leadership need to be changed. Paradoxical leadership behavior may seem inconsistent and contradictory, but it achieves a balance by equally paying attention to the individual needs of employees and taking care of organizational growth and development. This study examined the relationship between paradoxical leadership and employee creativity taking in to account the moderating role of employee mindfulness and mediating role of absorptive capacity. The study is grounded on Componential theory of creativity which is a comprehensive model of the social and psychological components necessary for an individual to produce creative work. Design/methodology/approach- Data was collected from the managers of different companies operating in Oil and Gas sector of Pakistan using questionnaires. Findings- This study provides evidence for a predictive relationship between paradoxical leader and employee creativity under the mediating role of absorptive capacity. Additionally, the moderating role of employee mindfulness is not established in this context of the Oil and Gas Sector of Pakistan. Practical implication- Leadership working in organizations of Oil and Gas sector must give opportunities to their employees so that they can demonstrate creative behavior and find new ways of working. Originality/value- This study offers new theoretical and practical insights by empirically investigating the mediating role of absorptive capacity between Paradoxical leadership and employee creativity in the existing literature. Furthermore, this study will help managers and leaders to allow employees to be more creative in this complex and dynamic environment.